CORRELATION BETWEEN DIGITAL LITERACY AND EMOTIONAL INTELLIGENCE ON UNDERSTANDING VISCOSITY STOKE'S METHOD AIDED BY VLAB AMRITA OLABS - Riki Purnama Putra; Ade Yeti Nuryantini; Pina Pitriana; Rena Denya Agustina (Journal of Teaching and Learning Physics, 2023)
Digital literacy is an understanding of digital which is an ability that is very much needed in learning in the digital era or the 21st century. The use of technology or technology development is one of the things that can be used in digital literacy skills. The use of technology in education is the most important aspect of 21st-century learning because many students have started using technology, one of which is virtual-based laboratory activities. Not spared from digital literacy, a person's success in the 21st Century is determined by his emotional intelligence. About 80% of emotional intelligence (EQ) is the main factor in a successful life. This study aims to find a correlation between digital literacy and emotional intelligence using Viscosity Stoke's Method assisted by the Amrita OLabs virtual laboratory. For digital literacy aspect there are; (1) Internet Basic; (2) Use of Win/Mac OS; and (3) Computer Basic, for emotional intelligence, the aspect there are; (1) Perception; (2) Understanding; (3) Facilitation; and (4) Self-Management. The method used in this research is using a true-experimental one-group pretest-posttest design, with a sampling technique that is non-probability sampling which produces a purposive sample of 30 subjects in the early semester students of Physics Education UIN Sunan Gunung Djati Bandung. The results showed that there was an influence on digital domain literacy on N-Gain and emotional intelligence with N-Gain. In addition, the Pearson's Correlation test shows a correlation between digital domain literacy and emotional intelligence, which is indicated by a sig value of .039 with a low degree of correlation or Pearson's correlation value of .379. This research has implications for determining the decision to use a virtual laboratory to increase digital literacy in terms of student’s emotional intelligence